Nutritional rickets: nature or nurture? - BEREKET, ABDULLAH (My University, 2006)
Rickets is a mineralization disorder of the growing bone. Nutritional rickets is still prevalent in many parts of the world. Although vitamin D deficiency plays a central role in the pathogenesis of this disease, calcium deficiency and genetic factors may also cause or contribute to the development of rickets. This review will focus on the classical form of nutritional rickets: vitamin D deficiency rickets. Epidemiology, ethiopathogenesis, risk factors, the current clinical picture, diagnosis, treatment and prevention of nutritional rickets will be reviewed.
Keywords: rickets; vitamin D; bone; calcium; cholecalciferol